153k views
1 vote
Simplify each expression

Simplify each expression-example-1
User Maxem
by
4.6k points

2 Answers

6 votes

Answer:

The correct answer is,

(10y² + 15y)/(35y² - 5y) = (2y + 3 )/( 7y - 1)

Explanation:

It is given an expression,

(10y² + 15y)/(35y² - 5y)

To simplify the given expression

Taking 5y as common from both numerator and denominator,

(10y² + 15y )/( 35y² - 5y) = 5y( 2y + 3)/5y( 7y - 1)

= (2y + 3 )/( 7y - 1)

Therefore the simplified form of given expression is given by,

(10y² + 15y)/(35y² - 5y) = (2y + 3 )/( 7y - 1)

User Alphanumeric
by
4.3k points
3 votes

Answer:


(2y+3)/(7y-1)

Explanation:

The given expression is


(10y^2+15y)/(35y^2-5y)

Factor both the numerator and the denominator.


=(5y(2y+3))/(5y(7y-1))

Cancel out the common factors.


=(2y+3)/(7y-1)

User Mdk
by
4.6k points